Scattering-aware texture reproduction for 3D printing - Elek, Oskar; Sumin, Denis; Zhang, Ran; Weyrich, Tim; Myszkowski, Karol; Bickel, Bernd; Wilkie, Alexander; Krivanek, Jaroslav (ACM Transactions on Graphics, 2017)
Color texture reproduction in 3D printing commonly ignores volumetric light transport (cross-talk) between surface points on a 3D print. Such light diffusion leads to significant blur of details and color bleeding, and is particularly severe for highly translucent resin-based print materials. Given their widely varying scattering properties, this cross-talk between surface points strongly depends on the internal structure of the volume surrounding each surface point. Existing scattering-aware methods use simplified models for light diffusion, and often accept the visual blur as an immutable property of the print medium. In contrast, our work counteracts heterogeneous scattering to obtain the impression of a crisp albedo texture on top of the 3D print, by optimizing for a fully volumetric material distribution that preserves the target appearance. Our method employs an efficient numerical optimizer on top of a general Monte-Carlo simulation of heterogeneous scattering, supported by a practical calibration procedure to obtain scattering parameters from a given set of printer materials. Despite the inherent translucency of the medium, we reproduce detailed surface textures on 3D prints. We evaluate our system using a commercial, five-tone 3D print process and compare against the printer’s native color texturing mode, demonstrating
CRIS-Team Scopus Importer:2022-07-26
Keywords: Appearance enhancement; Appearance reproduction; Computational fabrication; Sub-surface light transport